PENGARUH PERCEIVED USEFULNESS DAN PERCEIVED EASE OF USE TERHADAP PENERIMAAN TEKNOLOGI PADA GENERASI MILLENNIAL - Martha, Marcia; Fuad, Afmi; Prabawati, Ira Norma; Ratih, Poppy Dewi; Damariyanti, Meta (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The beginning for the successful implementation of information and communication technology is the willingness to accept the technology among users, especially among generasi millennial. This research was conducted to determine the influence of perceived usefulness and perceived ease of use on the acceptance of technology. This research uses a library research method based on a quantitative approach with the respondents used in this study are millennial aged 20-30 years and have accessed e-commerce applications through their smartphones. The results showed that perceived usefulness and perceived ease of use jointly influence the acceptance of technology. With the characteristics of the millennial generation as technology users, the higher the level of perceived usefulness and perceived ease of use, the higher the acceptance of technology.